النظام المحاسبي المطبق في المصرف الزراعي التعاوني وآلية تطويره (مجلة جامعة اللاذقية- سلسلة العلوم الاقتصادية والقانونية, 2019)
تنبع أهمية الأنظمة المحاسبية المطبقة في المصارف من كونها تشكل أساساً لتسجيل ومعالجة العمليات المصرفية،هذا و يتولى المصرف الزراعي عملية التخطيط المركزي للائتمان الزراعي والتمويل التعاوني والعمل على تمويل هذا الائتمان وتوفير كافة مستلزمات الإنتاج بالإستيراد أو من الإنتاج المحلي ويشارك في تنمية الاقتصاد الوطني، ومن هنا تأتي أهمية دراسة واقع النظام المحاسبي المطبق فيه وضرورة تطوير هذا النظام لضمان نوعية ما ينتجه من معلومات محاسبية تستخدم لتقييم نشاط المصرف. وبناء عليه فإن البحث يتناول آلية ومنهجية تطوير النظام المحاسبي الموحد المطبق في المصرف الزراعي  في ضوء التشغيل الالكتروني للبيانات المحاسبية وأتمتة النظام المحاسبي وبما يتلاءم مع متطلبات معايير المحاسبة الدولية ذات الصلة. وقد خلصت الدراسةإلى قصور النظام المحاسبي الموحد للمصارف وعدم ملاءمته لضخامة العمل في المصرف. ولكي يقوم المصرف بأداء أعماله ويلاحق التطورات في الخدمات المصرفية والأدوات المتاحة للعمل المصرفي يجب أن يقوم: باستبدال النظام المحاسبي المصرفي بنظام محاسبي الكتروني حديث،و استخدام التقنيات العالمية الحديثة في تعاملات المصرف داخلياً وخارجياً، والالتزام بتطبيق معايير المحاسبة الدولية . The importance of the accounting system applied in banks emerges from their being the ground for recording and processing the banking operations, the Agricultural Bank carries on the function of central planning for the agricultural credits and the cooperative financing and the work to finance this credit and provide all the production needs either by importing or from the local production, in addition to its participation in developing the national economy. This manifests the importance of studying the accounting system applied and the need to develop this system to guarantee the quality of the output accounting data that are employed to assess the activity of the bank. Consequently, this paper deals witlh the means and methods of updating the unified accounting system applied in the agricultural bank, in the light of automation of the accounting system and in accordance with the requirements of the related international accounting standards . This paper reached to find failures in the unified accounting system of the banks and its being inappropriate to the huge load of work in the bank. For the bank to work effeciently, it must do the following; replace the banking accounting system with a modern electronic one, employ the advanced international technology in handling the local and foreign transactions of the bank, and apply the international accounting standards.